Genetic variants in GRHL3 and risk for neural tube defects: A case–control and case–parent triad/control study. Issue 19 (22nd July 2019) - Yang, Wenlei; Xiao, Yanhui; Tian, Tian; Jin, Lei; Wang, Linlin; Ren, Aiguo
Abstract: Background: Neural tube defects (NTDs) are the most common severe birth defects with complex etiologies. Previous studies conducted on animals have suggested that the Grhl3 gene is essential for closure of the spinal neural tube, but little evidence from human studies on the variants of GRHL3 gene has been provided, especially the common genetic variants. Methods: To investigate the relationship between common genetic variants of GRHL3 and the risk for NTDs, we performed a case–control study and a case–parent triad/control study. Fast‐target enrichment sequencing was performed to screen exon regions from 503 NTD cases, and three tag SNPs (single nucleotide polymorphisms, including rs12030057, rs2486668, and rs545809) were selected according to the sequencing results. Then, Sequenom MassARRAY genotyping was performed in 757 case parents and 519 controls to obtain genotype information of the target variant sites among all NTD triads and controls. Results: The genotype distributions of all SNPs were in accordance with Hardy–Weinberg Equilibrium (HWE) in the control population. In the case–control study, significant associations were found between C27G genetic variants on rs2486668 and risk for spina bifida and encephalocele, respectively, under different genetic models. Consistently, in the case–parent triad/control study, GG genotype on rs2486668 was associated with increased risk for spina bifida, with a RR of 2.15 (95% CI: 1.20–3.83). However, no parent‐of‐origin effect was found for any tag SNPs. Conclusion: The GRHL3 C67G missense variant may increase the risk for spina bifida and encephalocele phenotypes.